Key sugar transporters drive development and pathogenicity in Aspergillus flavus - Yasin, Raheela; Usman, Sayed; Qin, Qijian; Gong, Xiufang; Wang, Bin; Wang, Linqi; Jin, Cheng; Fang, Wenxia (Frontiers in Cellular and Infection Microbiology, 2025)
Aspergillus flavus is a ubiquitous filamentous fungus that poses significant threats as both a causative agent of invasive aspergillosis and a major source of crop contamination due to production of aflatoxin B1 (AFB1). Sugars are essential for fungal metabolism, cell wall biosynthesis, and virulence, yet sugar transporters (STPs) in A. flavus remain largely uncharacterized. In this study, we systematically investigated three putative STP genes (G4B84_001982, G4B84_005374, and G4B84_009351) by comprehensive functional characterization of gene deletion mutants. Growth assays revealed that G4B84_001982 and G4B84_005374 mediate uptake of diverse sugar substrates, while G4B84_009351 appeared to be non-essential under tested conditions. Heterologous expressions in the hexose transport-deficient Saccharomyces cerevisiae strain confirmed their sugar transporter activity. Phenotypic analysis revealed that the Δ1982 and Δ5374 mutants showed pleiotropic defects, including impaired growth, reduced sporulation, delayed germination, increased sensitivity to cell wall stressors, and completely abolished sclerotium formation. Pathogenicity assays demonstrated that the two mutants exhibited attenuated virulence in both plants (crop seeds) and animal (Galleria mellonella) infection model. Our findings highlight the essential of two STPs in A. flavus development, stress tolerance, and pathogenicity, offering insights into sugar-mediated pathogenicity in this economically and medically important fungus.